The materiality of texts from ancient Egypt: new approaches to the study of textual material from the Early Pharaonic to the Late Antique period - Hoogendijk, F. A. J.; Gompel, Steffi M. T. van (Papyrologica Lugduno-Batava, 2018)
The material authority of written texts in pharaonic Egypt /Christopher Eyre --The platypus paradox: an archaeological approach to ancient Egyptian writing practices /Massimiliano S. Pinarello --Telling them by their hands: what palaeography has to offer prosopography /Rodney Ast --The body of the king and of the goddess: materiality in and through manuals for pharaoh from Tebtunis /Susanne Topfer --Material matters: documentary papyri and ostraca in late Ramesside Thebes /Ben Haring --Writing on ostraca: considerations of material aspects /Julia Lougovaya --Ceramic supports and their relation to texts in two groups of ostraca from the Fayum /Clementina Caputo and James M.S. Cowey --Evolving epigraphic standards in the field: documenting late and Graeco-Roman Egyptian graffiti through photogrammetry at Elkab / Luigi Prada and Paul D. Wordsworth --Revealing the material world of ancient writing: digital techniques and theoretical considerations /Kathryn E. Piquette.